2022
DOI: 10.1021/acs.jchemed.2c00096
|View full text |Cite
|
Sign up to set email alerts
|

Virtually Bridging the Safety Gap between the Lecture Hall and the Research Laboratory

Abstract: Laboratory safety has received heightened attention due to a series of devastatingly tragic accidents in both academic and nonacademic settings. Consequently, chemistry departments at various academic institutions now offer some form of formal training in laboratory safety for entering graduate students. Although the extent of this training varies widely among institutions, it typically includes an online assessment and/or minimal in-person classroom instruction. However, a significant gap exists between a lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Other formats (VR headsets) offer the possibility of a more immersive experience. However, in spite of potential distractions that may be more prevalent in laptop/desktop mode, we previously found that students viewing the VR modules on computer screens nonetheless reported a sense of presence in the virtual environment . An additional limitation of this study may be a consequence of the different interactions that the leaders and members had with the virtual laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other formats (VR headsets) offer the possibility of a more immersive experience. However, in spite of potential distractions that may be more prevalent in laptop/desktop mode, we previously found that students viewing the VR modules on computer screens nonetheless reported a sense of presence in the virtual environment . An additional limitation of this study may be a consequence of the different interactions that the leaders and members had with the virtual laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently described the creation of VR experiences that are designed to bridge the safety gap between lecture hall learning and best practices in the research laboratory. 8 In brief, we installed a variety of safety hazards in several subdisciplinefocused lab settings, including organic, inorganic, laser, medicinal, and screening/chemical biology environments. These laboratories were imaged with a 360°camera and assessment features were incorporated into the VR modules using the Unity engine.…”
Section: ■ Methodologymentioning
confidence: 99%
“…31,39,40 Laboratories and research centers are among the principal centers for using and consuming hazardous chemicals. 41 In these settings, the staff and students are not only constantly and chronically exposed to chemicals, but a wide variety of chemicals can be found. 42 Working in the laboratory environment is fraught with uncertainty in terms of preparing new materials and acquiring knowledge through innovative methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Laboratories and research centers are among the principal centers for using and consuming hazardous chemicals . In these settings, the staff and students are not only constantly and chronically exposed to chemicals, but a wide variety of chemicals can be found .…”
Section: Introductionmentioning
confidence: 99%
“…A major concern for the laboratory instructors at our college was that the online laboratory promote deep student content knowledge that enhances lecture material, provide safe experiments that could be performed hands-on at home, and allow for students to share scientific ideas together in group work. There were many options , for how to run an online lab following the COVID-19 shut-down, including synchronous (through web conferencing) or asynchronous at-home lab kits , (commercial or homemade), virtual lab simulators, synchronous or asynchronous live or recorded lab activities, dry lab data analysis, virtual reality laboratories, online digital lab modules, or choose your own adventure skill lab simulations . While there were many options to get students some laboratory-based experience with data analysis, a consideration not examined in any of these situations was how or if the students are learning hands-on laboratory techniques in these environments.…”
mentioning
confidence: 99%